Construction capital structure; soe and non-soe in the pandemic era - Nancy Megawati Hariandja; Hermanto Siregar; Arif Imam Suroso; Adler Haymans Manurung (Politeknik APP Jakarta, 2022)
This research aims to actuate the determinants of the capital structure of the state and non-state-owned construction industries during the infrastructure policy and the Covid-19 pandemic periods. Secondary data were collected quarterly from 2013 to 2020 from the Indonesia Stock Exchange (IDX), Bank Indonesia, and the Ministry of Public Works and Public Housing budget using a dynamic panel data with the Generalized Method of Moments. It was found that speed of adjustment, profitability, tangibility, activity, and infrastructure policies affect the capital structure of state-owned construction companies. Meanwhile, speed of adjustment, profitability, tangibility, and exchange rate affect non-state-owned construction companies. The result showed that state-owned and non-state-owned construction companies have a gap of 27.3% and 17.7% %, respectively. Furthermore, both companies have speed adjustment values of 1.38 period and 1.21 period. This means that non-state-owned construction companies' adjustment speed is faster than their state-owned counterpart. Therefore, the decision-making of debt construction companies needs to consider the financial characteristics and ownership of the company.